If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(3y + -5) = 1 + -4y Reorder the terms: 10 + -1(-5 + 3y) = 1 + -4y 10 + (-5 * -1 + 3y * -1) = 1 + -4y 10 + (5 + -3y) = 1 + -4y Combine like terms: 10 + 5 = 15 15 + -3y = 1 + -4y Solving 15 + -3y = 1 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 15 + -3y + 4y = 1 + -4y + 4y Combine like terms: -3y + 4y = 1y 15 + 1y = 1 + -4y + 4y Combine like terms: -4y + 4y = 0 15 + 1y = 1 + 0 15 + 1y = 1 Add '-15' to each side of the equation. 15 + -15 + 1y = 1 + -15 Combine like terms: 15 + -15 = 0 0 + 1y = 1 + -15 1y = 1 + -15 Combine like terms: 1 + -15 = -14 1y = -14 Divide each side by '1'. y = -14 Simplifying y = -14
| 3u+-7=-13 | | -2x+23=2x+11 | | 2x+3x-1+2x+3x-1= | | 4(k-6)=2(k+2) | | 5(3m-2)-(m-3)=13-4(-4m+5) | | 10-(2z-6)=4-3z | | 6a+3=2a-13 | | 4.4y=-88 | | -6x+56=-9-31 | | 2(-3)=76 | | 9.2y=-88 | | 0.71*x=3 | | 2n+5=(n-2)-n | | 8=2x-3y | | 3(3v-2)=4(2v+2) | | 2X+1-4=-2X-34 | | 4z/10+7=8 | | 12x=2x+10x+1 | | 3m-8m=110 | | x/9+3=6 | | 9(1.082x+1)=15 | | z/7+3=6 | | 15x^2-47x-10=0 | | 137-(6x+5)=6(x+9)+x | | 2/3x–6=9 | | 5x-4=x+3*2 | | 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x |